(383) The Appraisal of Investment Projects تقييم المشاريع الاستثمارية - Timbergen, J. (معهد التخطيط القومى, 2024)
This study examines the methods for appraising economic projects within the framework of a national development plan. It emphasizes the importance of gathering information on individual projects to identify areas where the country holds a comparative advantage, contributing to national income growth. Projects include activities such as building factories, roads, schools, or implementing specific government policies. Detailed descriptions, technical specifications, and timelines are essential for project planning. The study highlights the need for two types of information: benefits expected from the project aligned with development goals, and costs involving the use of scarce resources. It underscores aligning benefits and costs to select projects that achieve development objectives with minimal sacrifices